A wideband highly efficient omnidirectional compact antenna for WiMAX/Lower 5G communications - Paul, Liton Chandra; Ankan, Sarker Saleh Ahmed; Rani, Tithi; Karaaslan, Muharrem; Hossain, Md. Najmul; Al Gburi, Ahmed Jamal Abdullah; Saha, Himel Kumar; Alkurt, Fatih Özkan (John Wiley & Sons Inc., 2023)
Microstrip patch antenna (MPA) is widely used for different wireless communications such as WiMAX and fifth generation (5G). In this paper, a wideband, highly efficient, omnidirectional, compact novel patch antenna has been designed and reported for WiMAX/lower 5G communications. The proposed compact MPA is made on Rogers RT 5880 (ɛr = 2:2 and tan ðδÞ = 0:0009). The physical volume of the MPA is compact (32 × 32 × 0:79 mm3). The MPA consists of seven small square-shaped elements that are diagonally connected with each other. The 7-element antenna works at 3.592 GHz with a suitable reflection coefficient of -46.78 dB and a -10 dB bandwidth (BW) of 1.40 GHz, covering 3.10-4.50 GHz. The apex gain (G) and the directivity (D) of the designed prototype are 3.90 dB and 4.20 dBi, respectively. The antenna maintains a high efficiency of 94-98% over the 3.10-4.50 GHz operating range. The VSWR of the antenna is close to unity, which is 1.0092 at 3.592 GHz. Initially, CST is used to design the antenna, and then, all the properties have been buttressed by using high frequency structure simulator (HFSS). Finally, a prototype of the compact 7-element antenna has been developed and measured. Owing to getting good results for the intended applications, the presented compact antenna can be a reliable candidate for WiMAX (3.4-3.6 GHz) and lower 5G (3.3-4.2 GHz).